WHISTLEBLOWING IN CIVIL SERVICE: EXPERIENCE OF EUROPE - M. A. Batishcheva (MGIMO University Press, 2014)
In this article it is examined the whistleblowing practice in civil service across Europe. The analysis lets to arrive at a conclusion that the whistleblowing mechanism unevenly functions in different parts of Europe: it is more widespread in East and South. It is indicated the following reasons for that: differences in institutional systems of society, models of civil service («continental» and anglosaxon) and sociocultural distinctions. Based on the Hofstede dimensions of national culture it is noted that cultural characteristics correlate with presence/absence of whistleblowing law and practice and effectiveness of this mechanism as a whole. Focusing on the role of whistleblowing in control of deviations of civil servants' behavior, it is supposed that the whistleblowing needs to be implemented in the Russian civil service. Obstacles to the whistleblowing design and implementation were also shown and some recommendations were given, taking into account sociocultural characteristics of the Russian society.